Self-reliance and the rights to work for refugees: lessons from the case studies of South Africa and Germany for the implementation of the Global Compact on refugees by the European Union - Heiss, Marie-Isabelle (Department of Public Law, 2022)
The right to work is a fundamental human right and regarded essential for a life in dignity. It is explicitly granted to refugees in international and regional law, as well as in numerous national constitutions. In practice, however, refugees have to overcome many obstacles in order to participate in working life in the host country. This paper uses South Africa and Germany as case studies to explore causes and remedies for this discrepancy. To this end, the legal provisions regarding the right to work and their implementation in practice in South Africa and Germany are assessed against the respective socio-economic background. Subsequently, proposals for a coherent future EU policy on the access to work and the promotion of refugee self-reliance as driven by the UN Global Compact on Refugees are made. South Africa is the scene of an increasingly restrictive handling of traditionally generous refugee laws. Administrative or bureaucratic hurdles undermine the right of refugees to work or receive social benefits. Xenophobia often leads to further marginalization against the backdrop of high unemployment. In Germany, protective labour market regulations have been gradually relaxed since 2013 to address labour shortage. However, new restrictions were introduced in 2018 that make it more difficult for asylum seekers in particular to access the labour market. As in South Africa, the long duration of asylum procedures and processing backlogs keep them in limbo for a long time with very limited work opportunities. Legal scholars and researchers agree that the realization of the right to work can increase social cohesion by turning formerly aid-dependent refugees into integrated, self-reliant, and contributing members of their host society. This gives rise to the call for targeted support measures to provide more effective access to fair, paid work for refugees as early as possible. In implementation of the Global Compact on Refugees (GCR), the EU should lead by example by applying a protection-based approach in their own legislation and policies and support developing countries in promoting refugee's self-reliance.